ANALISIS BEBERAPA FAKTOR YANG MEMPENGARUHI KELENGKAPAN PENGUNGKAPAN LAPORAN KEUANGAN PERUSAHAAN JASA TRANSPORTASI, PERDAGANGAN DAN MANUFAKTUR YANG TERCATAT DI BURSA EFEK JAKARTA - DEWI AGUSTINA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2006)
The aim of this research is to find the factors that influence completeness of financial statement disclosures index. The independent variables are Profitability, Leverage, Percentage of Public Owned, and Status. The research used a purposive sampling method with 11 data of service transportation companies, 36 trading companies, and the last 69 data of manufacturing companies listed at Jakarta Stock Exchange in 2004-2005. The data analyzed by multiple regression. The result of the service transportation companies study showed that Profitability has significant influence toward completeness of financial statement disclosures index in 2004-2005, but Leverage, Percentage of Public Owned, and Status has not significant influence toward completeness of financial statement disclosures index. The result of the trading companies study showed that Leverage has significant influence toward completeness of financial statement disclosures index but profitability, Percentage of Public Owned and Status has no significant influence toward completeness of financial statement disclosures index in 2004-2005. The result of the manufacturing companies showed that Percentage of Public Owned has significant influence toward completeness of financial statement disclosures index but Profitability, Leverage, and Status has no significant influence toward completeness of financial statement disclosures index in 2004-2005.